Intra-African agricultural trade: Recent trends and nutritional content - Olivetti, Elsa; Collins, Julia; Odjo, Sunday P.; Laborde Debucquet, David (AKADEMIYA2063, 2023)
Increasing intra-African trade has long been an important development objective. The free movement of goods, services, factors of production, and people is seen as a key outcome of the African Union’s Agenda 2063, which expresses broad goals and aspirations for development and political and economic integration on the continent. The 2014 Malabo Declaration on Accelerated Agricultural Growth and Transformation for Shared Prosperity and Improved Livelihoods includes tripling intra-African agricultural trade by 2025 as one of seven major commitments. The African Continental Free Trade Area (AfCFTA), launched in January 2021, seeks to increase intra-African trade in order to boost industrial and socioeconomic development. With several important areas of the AfCFTA Agreement, including rules of origin, still under negotiation as of early 2023, the African Union adopted “Year of AfCFTA: Acceleration of the African Continental Free Trade Area Implementation” as its theme for 2023 in an effort to increase attention and commitment to the AfCFTA.